Acute spontaneous spinal subdural hematoma presenting with Takotsubo cardiomyopathy: a rare case report and literature review. Issue 5 (5th May 2022) - Xiang, Jie; Zhao, Weibo; Luo, Xiao; Hong, Zhenghua; Luo, Hua
Abstract : Spontaneous spinal subdural hematoma (SSDH) is a rare and dangerous intraspinal hematoma that usually occurs in the thoracic vertebra. The influence of early cardiovascular changes secondary to spinal cord injury is an important emergent issue. Herein, we report a case of a middle-aged woman with clinical manifestations of back pain and motion and sensory disturbances below the level of spinal cord compression. During the disease course, she also developed changes indicative of myocardial injury, such as tachycardia, markedly increased concentrations of brain natriuretic peptide and cardiac troponin I, and a decreased left ventricular ejection fraction, which were consistent with the diagnosis of Takotsubo cardiomyopathy (TTC). After the administration of supportive therapies, the symptoms of myocardial injury rapidly resolved. With the absorption of SSDH, the symptoms and clinical signs were alleviated. We also reviewed the literature on cases of concomitant SSDH and TTC. This rare case broadens the symptom spectrum of SSDH and highlights the need for clinicians to be aware of concomitant SSDH and TTC. Initial conservative treatment is a viable option for SSDH with concomitant TTC. However, urgent surgery may be a better option if the SSDH progressively enlarges and causes spinal cord compression.